Generation mode stability of a fiber ring laser - Gnatenko, A. S.; Machekhin, Yu. P. (Begell House, 2015)
To provide DWDM systems with a single source of radiation, it is possible to use a fiber femtosecond laser operating in the mode of generation supercontinuum. Functioning of a fiber ring laser operating in the mode of a train of ultra-short pulses is determined by the presence of liquid crystal polarizers being part of the resonator. Understanding of the control mode conception for passive mode locking by means of the liquid crystal polarizers is possible upon stable laser operating conditions. Therefore, it is purposed to study the conditions of sustainable modes of the ultra-short pulse fiber ring laser.
Keywords: fiber laser; non-linear amplification factor; coefficient of dispersion